Wskaźnikowa ocena rentowności banku - Kopiński, Adam (Indicative Assessment of a Bank's Profitability, 2005)
The paper presents the notion of a bank's profitability and the main types of profitability indicators in relation to the financial category, which are: the financial result (numerator) and the reference basis (denominator). It also analysis the profitability indicator pyramid which allows to distinguish the factors of profitability, as well as discusses the profitability of centres of responsibility (profit centres).(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 244-251